GLOBAL ECONOMIC RECESSION: CAUSES AND EFFECTS ON NIGERIA BUILDING CONSTRUCTION INDUSTRY - O. I., Olanrewaju; J.E., Idiake; L.O., Oyewobi; W. P, Akanmu (Journal of Surveying, Construction and Property, 2018)
In 2016, Nigeria’s real Gross Domestic Product (GDP) growth rate in the first quarter was -0.36% while the second quarter was -2.06% indicating economic recession. The purpose of this study is to examine the causes and the effects of economic recession on the building construction industry. The study adopted quantitative research approach by eliciting primary data through questionnaire which was administered to 244 respondents, of which 210 were returned and considered valid for further analysis. The data were analysed using descriptive statistics and relative importance index (RII) to rank the causes and effects of economic recession. The findings revealed three major causes of economic recession; unstable exchange rates (RII = 0.90), reduction in volume and price of crude oil (RII = 0.88) and excessive corrupt practices (RII = 0.78) while the three major effects of economic recession on the Nigeria building construction industry identified were; high rate of unemployment (RII = 0.93), high rate of bankruptcy (RII = 0.89) and reduction in mortgage lending rate (RII = 0.89). The study concluded that economic recession has negative effects on the Nigeria building construction industry. This study however recommends among other stability of exchange rate through devaluation, diversification of economy, transparency and amendment of mortgage institution policies Findings from this study could be used to develop strategies for mitigating against the effects of recession on the performance of the building industry.